2005
DOI: 10.1189/jlb.0604332
|View full text |Cite
|
Sign up to set email alerts
|

Development and functional consequences of LPS tolerance in sinusoidal endothelial cells of the liver

Abstract: Kupffer cells and liver sinusoidal endothelial cells (LSEC) clear portal venous blood from gut-derived bacterial degradation products such as lipopolysaccharide (LPS) without inducing a local inflammatory reaction. LPS tolerance was reported for Kupffer cells, but little is known whether sensitivity of LSEC toward LPS is dynamically regulated. Here, we demonstrate that LSEC react to LPS directly as a function of constitutive Toll-like receptor 4 (TLR4)/CD14 expression but gain a LPS-refractory state upon repet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(125 citation statements)
references
References 24 publications
7
118
0
Order By: Relevance
“…TLRs recognize a diverse range of pathogen-associated molecular patterns and play a critical role in antimicrobial host defense (1, 2); however, increasing evidence suggests the involvement of TLRs in the pathogenesis of human diseases, such as autoimmune diabetes, inflammatory bowel diseases, multiple sclerosis, or systemic lupus erythematosus (3,4). In liver, TLRs are widely expressed on Kupffer cells, hepatocytes, hepatic stellate cells, biliary epithelial cells, sinusoidal endothelial cells, and hepatic dendritic cells (DCs) (5)(6)(7)(8)(9)(10). Also, the liver is constantly exposed to gut-derived bacterial products, suggesting that bacterial products and TLRs might be involved in liver diseases.…”
Section: Tlr-9 Activation Aggravates Concanavalin A-induced Hepatitismentioning
confidence: 99%
“…TLRs recognize a diverse range of pathogen-associated molecular patterns and play a critical role in antimicrobial host defense (1, 2); however, increasing evidence suggests the involvement of TLRs in the pathogenesis of human diseases, such as autoimmune diabetes, inflammatory bowel diseases, multiple sclerosis, or systemic lupus erythematosus (3,4). In liver, TLRs are widely expressed on Kupffer cells, hepatocytes, hepatic stellate cells, biliary epithelial cells, sinusoidal endothelial cells, and hepatic dendritic cells (DCs) (5)(6)(7)(8)(9)(10). Also, the liver is constantly exposed to gut-derived bacterial products, suggesting that bacterial products and TLRs might be involved in liver diseases.…”
Section: Tlr-9 Activation Aggravates Concanavalin A-induced Hepatitismentioning
confidence: 99%
“…TLR4 and MyD88 are expressed on KCs, sinusoidal endothelial cells and hepatic stellate cells. 15,29,30 KCs are highly relevant for the production of vasoconstrictors in the intrahepatic microvasculature. 6,16 The effects observed in this study seem to be predominantly dependent on the KCs, because GdCl 3 pretreatment attenuated TLR4 and MyD88 expression after LPS pretreatment.…”
Section: Kc-dependent Effects Of Intraperitoneal Lpsmentioning
confidence: 99%
“…66,67 In vivo, however, LPS failed to elicit an inflammatory response in intrahepatic cholangiocytes. 63 This defect in response to the TLR4 ligand, referred to as "TLR tolerance", has been described in macrophages and represents a natural defense mechanism from gut-derived endotoxin. 68,69 Harada et al 70 identified that human cholangiocytes develop tolerance to TLR2 and TLR4 ligands via induction of IRAK-M, a negative regulator of TLR signaling.…”
Section: Prrs In Liver Diseasesmentioning
confidence: 99%
“…61 Endothelial cells, lining the hepatic sinusoids, constitutively express TLR4 and upregulate NF B activity, produce pro-inflammatory cytokine (TNF␣) and ROS in response to TLR4-mediated LPS stimulation. 62,63 Biliary epithelial cell lines (MMNK-1, MZChA-1 and H-69) and biliary epithelium in vivo expressed mRNA for all TLRs, the co-receptor, MD-2 and negative regulators of TLR signaling (Tollip, SIGGIR and ST-2). 64,65 TLR2, 3, 4 and 5, but not TLR7, 8,9, were detected at the protein level and appeared functionally active based on ligand-induced IL-6, IL-8 and MCP-1 production in biliary epithelial cell lines.…”
Section: Prrs In Liver Diseasesmentioning
confidence: 99%